Disclosure and Measurement of Accounting on Human Capital and their Effect on Increasing the Value of Economic Unit, it is an Applied Study on AL-Doha Factory of Cement Industries Ltd/Al- Muthana Province/Iraq (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to measure human capital and economic units through the use of human development expenses of intellectual appropriation, regardless of the accounting disclosure of the value of human capital in the general balance sheet of the economic units. Which leads to increasing the value of the economic unit and its roots. And for making the objective of this study, some accounting statements (general balance sheets and payroll and wages) belonging to ALDOHA Factory of Cement Industries Ltd. in AL-MUTHANA Province for the year (2013) were used for disclosure and measurement of human capital in its capital list. The study concluded that there is an opportunity to have economic units for payment by accounting for any physical process of human capital by relying on earmarks, no concession for accounting disclosure about human capital in the balance sheet, and an economic unit list. The study also found that there is a role for qualifications accounting disclosure about human capital and an economic unit in the listed improvements. The researchers recommended the need to accelerate the attention and an economic unit of human capital, since this element constitutes an interest in language as one of the elements of suitable productive contributions, in addition to adopting the necessary methods and standards that serve to undertake any physical and accounting disclosure about human capital in the financial lists.